The economic value of Indonesia's tropical rainforest park (TH2TI) in South Kalimantan - Rezekiah, Arfa Agustina; Fithria, Abdi; Shiba, Yasinta Nur; Ilham, Wahyuni (Foresty Faculty of Hasanuddin University, 2024)
Urban forest is a form of environmentally oriented development. One form of urban forest in South Kalimantan is the Indonesia’s Tropical Rain Forest Park (TH2TI). This study aims to calculate the total economic value and future value of TH2TI. The total economic value calculated in this study consists of direct use value (recreation, wood, carbon and oxygen), indirect use value (water absorption), and option value (existence and heritage). The method used in this research was quantitative research method to calculate the value of wood, carbon, oxygen, and water absorption and qualitative research method to calculate the value of recreation, existence, and heritage. Results indicated that the economic value of recreation was the highest amounted to IDR 1,568,514,750.00 and the total economic value of TH2TI amounted to IDR 3,085,373,964.75. In the next 5 years, the economic value of TH2TI could reach IDR 3,664,456,405.74. The knowledge of the economic values of TH2TI is expected to make people aware to the importance of the environment for life.